THE INFLUENCE OF PRINCIPALS’ PROFESSIONAL COMPETENCE, TEACHERS’ MOTIVATION, AND ORGANIZATIONAL CULTURE ON SCHOOL QUALITY - Linarto; Ngasbun Egar; Rosalina Br Ginting (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to analyze the influence of principals’ professional competence, teachers’ work motivation, and organizational culture on school quality at public senior high schools in Blora Regency. Using a quantitative approach with a correlational design, data were collected from 200 teachers through Likert-scale questionnaires. The results show that all three variables have a positive and significant effect on school quality, both partially and simultaneously, with a determination coefficient of 64.8%. The findings indicate that the professional competence of school principals strengthens instructional leadership, teachers’ work motivation enhances performance, and a strong organizational culture fosters collaboration and commitment to continuous improvement. The novelty of this study lies in the integration of leadership competence, teacher motivation, and organizational culture as internal determinants of school quality at the district level. This research contributes to developing a comprehensive model for improving educational quality through human resource synergy within schools.